Ludw. v. Beethoven - Bollinger, Friedrich Wilhelm, 1777-1825 (engraver):::Creator::::::::::::; Höfel, Blasius, 1792-1863 (artist):::Contributor::::::::::::; Letronne, Louis René, 1790-1842 (artist):::Contributor:::::::::::: (Germany; Gebrüder Schumann; Zwickau)
Engraving by Friedrich Wilhelm Bollinger after the engraving by Blasius Höfel based on the drawing by Louis René Letronne.